Genetic and Morphological Identification of Spirometra decipiens in Snakes and Domestic Dog Found in Cuba - Alexander Morales; Rebeca M. Laird-Pérez; Virginia Capó; Enrique Iglesias; Luis Fonte; Arturo Plascencia-Hernández; Enrique J. Calderón; Keeseon S. Eom; Yaxsier de Armas; Héctor R. Pérez-Gómez (Pathogens, 2022)
Spirometra (Cestoda: Diphyllobothriidea) affects humans and some species of domestic and wild animals which eventually interact with humans. In this article, we report three new cases of Spirometra decipiens (Diesing, 1850) infection observed in two intermediate hosts and one definitive host, in Cuba. Genetic and morphological identification of S. decipiens in two snakes and a domestic dog were carried out by molecular means and routine histological study using hematoxylin–eosin staining, respectively. Taken together, the anatomical location, the host species infected with the specimens and their morphological and genetic features, all the samples were identified as S. decipiens. In each of the three cases, PCR assays using specific primers amplified bands that corresponded to S. decipiens species. To our knowledge, this paper is the first report of S. decipiens in species of Cuban endemic fauna and in the Caribbean islands. These species constitute a real or potential risk of transmission of Spirometra to humans in Cuba.